Modified sediments and subsurface hydrology in natural and recreated salt marshes and implications for delivery of ecosystem services. Issue 10 (24th October 2014) - Tempest, James A.; Harvey, Gemma L.; Spencer, Kate L.
Abstract: Recreation or restoration of salt marsh through the deliberate removal of flood defences (managed realignment or de‐embankment) is a common practice across Europe and the USA, with potential to enhance delivery of ecosystem services. However, recent research suggests that physical, chemical and ecological processes may be impaired in recreated sites as a result of the modified morphology, sediment structure and hydrology associated with both the restoration process and historic land use. This paper compares physical sediment properties and subsurface water levels recorded in paired natural and de‐embanked (recreated) salt marshes in SE England. Using a combination of statistical and time‐series modelling, significant differences between the natural and recreated marshes are identified. Sediment properties (bulk density, moisture content and organic content) within each marsh were statistically different and imply that de‐embanked sediments are compacted, which may affect subsurface water movement. Analysis of hydrological time series reveals that the de‐embanked salt marsh is characterized by a damped response to tidal flooding with elevated and less variable water levels. This, combined with analysis of hydrographs and hysteresis patterns over individual tidal cycles, suggests that fast, horizontal near‐surface flows enhanced by the relict land surface may play a greater role in drainage of the de‐embanked salt marsh. The importance of hydrological functioning in governing many important physical and biogeochemical processes in salt marshes suggests any modifications would have significant implications for the delivery of ecosystem services. Copyright © 2014 John Wiley & Sons, Ltd.